2005
DOI: 10.1111/j.1600-0668.2004.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of air-conditioning with respiratory symptoms in office workers in tropical climate

Abstract: This study suggests that indoor air-related respiratory symptoms are a matter of concern in places with hot and humid climate. The regression models were adjusted by confounders that could be used in further reanalysis of indoor air quality related symptoms and ventilation systems with expanded variety of climatic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 27 publications
0
32
0
6
Order By: Relevance
“…People spend 80À90% of their time indoors, and indoor environment has important effects on human health and work efficiency. The factors affecting indoor environment mainly include temperature, humidity, air exchange rate, air movement, ventilation, particle pollutants, biological pollutants, and gaseous pollutants (Graudenz et al, 2005). By analyzing recent studies, Seppanen and Fisk (2002) found that there was an increase in prevalence of sick building syndrome (SBS) between 30% and 200% in the buildings with air-conditioning systems when compared with natural ventilation systems.…”
Section: Introductionmentioning
confidence: 99%
“…People spend 80À90% of their time indoors, and indoor environment has important effects on human health and work efficiency. The factors affecting indoor environment mainly include temperature, humidity, air exchange rate, air movement, ventilation, particle pollutants, biological pollutants, and gaseous pollutants (Graudenz et al, 2005). By analyzing recent studies, Seppanen and Fisk (2002) found that there was an increase in prevalence of sick building syndrome (SBS) between 30% and 200% in the buildings with air-conditioning systems when compared with natural ventilation systems.…”
Section: Introductionmentioning
confidence: 99%
“…3 This increased movement can lead to increased exposure to different indoor and outdoor conditions with wide range and sudden temperature changes. The presence of air conditioning systems 1,4,5 and atopic phenotype [6][7][8] are risk factors consistently associated with mucosal symptoms in IAQ epidemiologic studies. Interestingly enough, most studies do not find causal allergen exposure in nonresidential and nonindustrial settings.…”
mentioning
confidence: 98%
“…IAQ-related problems are reported in various climatic conditions including tropical climates, 1 and are considered the most common environmental health issue faced by clinicians. 2 The factors associated with IAQ have a complex interaction and include temperature, humidity, air exchange rates, exposure to organic and inorganic indoor air pollution, odors, air movement, and work and psychosocial factors.…”
mentioning
confidence: 99%
“…Indoor environment has important effects on human health and work efficiency. The factors affecting indoor environment mainly include temperature, relative humidity, indoor air quality, illumination, ventilation Graudenz et al [1]. Indoor air environments must meet the requirement of thermal comfort and Indoor Air Quality (IAQ).…”
Section: Literature Reviewmentioning
confidence: 99%